Clinical evaluation of post-surgical scar hyperaesthesia: a longitudinal observational pilot study - Donna L. Kennedy; Shehan Hettiaratchy; Caroline M. Alexander (SAGE Publishing, 2024)
Introduction The mechanisms underlying persistent scar pain are not fully elucidated and evidence for the clinical evaluation of scar pain is limited. This pilot observational study investigated participation data and sought to identify objective clinical scar evaluation measures for future trials. Methods With ethical approval and consent, adults undergoing planned hand surgery were enrolled from one NHS hospital. At 1- and 4-months post-surgery scar thermal and mechanical pain thresholds were evaluated with quantitative sensory testing; peri-scar inflammation with infrared thermometry and pliability with durometry. Participation data were analysed with descriptive statistics; the association of clinical measures with patient reported scar pain was analysed. Results Twenty-one participants (22% eligible patients) enrolled before study closure due to the COVID-19 pandemic; 13 completed follow up. No adverse events or dropouts resulted from clinical scar evaluation. Seventy percent of participants reported undertaking topical, nonprescription scar treatment independently. Neuropathic Pain Symptom Inventory (NPSI) scores were dispersed across the score range, capturing variability in participant-reported scar symptoms. Scar morphology, pliability and inflammation were not associated with scar pain. Differences between scar and contralateral skin in thermal and mechanical pain sensitivity were identified. Conclusion People with acute hand scars participate in clinical research and independently initiate scar treatment. Clinical testing of acute post-surgical hand scars is well tolerated. The NPSI demonstrates utility for exploring scar pain symptoms and may support the elucidation of mechanisms of persistent scar pain. Clinical tests of thermal and mechanical and sensitivity are promising candidate clinical measures of scar pain for future trials. Lay Summary Background: it is unknown why some scars remain painful long-term. We do not know if scar flexibility, inflammation or sensitivity to temperature or pressure relate to scar pain. We investigated if patients would enrol in scar research, if scar testing was tolerated and if clinical tests are useful for future scar studies. Study conduct: with ethical approval and consent, adult hand surgery patients were enrolled from one NHS hospital. Scar pain, inflammation and response to thermal, sharp and pressure tests were assessed at 1- and 4-months after surgery. Statistically, we analysed study participation, tolerance for clinical scar tests and if the scar tests related to scar pain. Findings: 21 participants (22% eligible patients) enrolled before study closure due to the COVID-19 pandemic; 13 completed follow up. No participants were injured due to scar testing. 70% of participants reported treating their scar independently. Neuropathic Pain Symptom Inventory (NPSI) allows participants to give a broad range of answers about their scar symptoms. Scores for clinical tests of scar flexibility and inflammation did not relate to participant-reported scar pain. Scars were more sensitive to tests of pin prick and cold than unaffected skin. What we learned: people with new hand scars participate in research and independently initiate scar treatment. Clinical testing of post-surgical hand scars is well tolerated. The NPSI is useful for exploring scar pain symptoms and may help us to learn about persistent scar pain. Pinprick and cold clinical tests may be useful objective pain tests for future scar research.